2022
DOI: 10.1088/1361-6528/ac9da8
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient In2S3/Ag2S/TiO2 NTAs photoelectrodes for photocathodic protection of Q235 carbon steel under visible light

Abstract: A novel In2S3/Ag2S/TiO2 nanotube arrays (NTAs) was successfully fabricated by successive ionic layer adsorption and reaction (SILAR) method and electrochemical anodic oxidation method, and served as photoanode for photocathodic protection application. The micromorphologies, optical absorption properties, crystalline structure and elemental valence states of the composites were performed by field emission scanning electron microscopy, high resolution transmission electron microscope, UV−vis diffuse reflectance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The photogenerated electrons in g-C 3 N 4 migrate unidirectionally to the protected metal, thus preventing the corrosion of the matrix. Li et al prepared a ternary In 2 S 3 /Ag 2 S/TiO 2 system. In 2 S 3 and Ag 2 S enhance the absorption of visible light, so the nanocomposites are coupled with carbon steel and the photocurrent density reaches 211 μA·cm –2 , which is about 4.5 times higher than that of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The photogenerated electrons in g-C 3 N 4 migrate unidirectionally to the protected metal, thus preventing the corrosion of the matrix. Li et al prepared a ternary In 2 S 3 /Ag 2 S/TiO 2 system. In 2 S 3 and Ag 2 S enhance the absorption of visible light, so the nanocomposites are coupled with carbon steel and the photocurrent density reaches 211 μA·cm –2 , which is about 4.5 times higher than that of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…When increasing deposition cycles, irregular aggregation of SnS 2 is produced on the surface of the TiO 2 coating. Li et al 91 prepared In 2 S 3 /Ag 2 S/TiO 2 heterojunction coatings utilizing the two-step SILAR method. The XRD results indicated that the prepared coating has a high purity.…”
Section: Silar Methodmentioning
confidence: 99%
“…Under white light illumination, the composite film photoanode lowered the potential of coupled 403 SS in a 0.5 M NaCl solution by 680 mV, showcasing a markedly enhanced effect of photo-electro-chemical cathodic protection. Li et al [27] successfully prepared a novel In 2 S 3 /Ag 2 S/TiO 2 nanotube array using continuous ion layer adsorption and electrochemical anodic oxidation methods and applied it as a photoanode for photo-electro-chemical cathodic protection. The study showed that compared to pure TiO 2 , the In 2 S 3 /Ag 2 S/TiO 2 nanocomposite exhibited better photoelectrocatalytic and photo-electro-chemical cathodic protection performance.…”
Section: Semiconductor Compounding Technologymentioning
confidence: 99%